Psilocybin-Assisted Therapy in Depressive Disorders: Efficacy, Safety, and Persistence of Clinical Effects — A Narrative Review - Zachar, Kinga; Sito, Maksymilian; Jurkowski, Filip; Wójcik, Łukasz; Gawron, Natalia; Bojanowski, Hubert Tomasz; Dobracka, Aleksandra; Marczak, Zuzanna; Jarowicz, Monika; Czmyr, Jędrzej (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Depressive disorders, particularly major depressive disorder (MDD) and treatment-resistant depression (TRD), remain major causes of disability worldwide. Conventional treatments are limited by delayed onset, incomplete response, relapse, and adverse effects. This review summarizes current evidence on the efficacy, safety, and durability of psilocybin-assisted therapy in depressive disorders. Brief description of the state of knowledge: Evidence from randomized trials, open-label studies, follow-up analyses, and meta-analyses indicates that psilocybin-assisted therapy can produce rapid reductions in depressive symptoms, often within days, in carefully selected patients treated in controlled settings. Short-term benefits have been reported in both MDD and TRD, although findings in TRD are less consistent. In a head-to-head trial, psilocybin was not superior to escitalopram on the primary endpoint, while several secondary outcomes favored psilocybin. Follow-up studies suggest that benefits may persist for weeks to months, but longer-term evidence remains limited and heterogeneous. Under supervision, psilocybin was generally well tolerated, with mostly transient adverse effects, including anxiety, nausea, headache, dizziness, and brief cardiovascular activation. Summary: Psilocybin-assisted therapy appears to be a promising investigational approach for depressive disorders, with rapid onset and possible medium-term benefit in some patients. However, the evidence base remains limited by small samples, heterogeneous designs, restricted comparative data, and delivery in specialized settings. Larger and longer-term studies are needed to clarify comparative efficacy, durability, long-term safety, and feasibility in routine clinical practice.